Interpreting the Synoptic Narratives of Jesus' Passion Today: A Challenge for Exegesis - Aletti, Jean-Noël (Biblica, 2023)
This article is methodological and was motivated by the recent publication of three monographs on the Synoptics and questions their interpretation of the narratives of Jesus’ passion and death. It is shown that one cannot correctly and faithfully account for these narratives (i) if one ignores the models that underlie and structure them, and (ii) if the model proposed is not that of the Evangelists.